The Effects of Anemia and Blood Transfusion on Patients With Stage III-IV Ovarian Cancer. Issue 9 (1st November 2013) - Altman, Alon D.; Liu, Xiao-Qing; Nelson, Gregg; Chu, Pamela; Nation, Jill; Ghatage, Prafull
Abstract : Objectives: The objective of this study was to examine the overall and recurrence-free survival in patients with advanced ovarian cancer based on hemoglobin and blood transfusions. Methods: A retrospective chart review was performed between 2003 and 2007 on patients with pathologically confirmed stage 3–4 ovarian, fallopian, or peritoneal cancers. Data were collected on date of diagnosis, recurrence and death, stage, grade, age, surgery, estimated blood loss, hemoglobin (nadir and average levels), and number of blood transfusions. Results: Two hundred sixteen patients were included in the final analysis. In the perichemotherapy, perioperative, and total time frames, 88%, 81%, and 95% of patients were anemic, and 9%, 22%, and 26% of the patients had severe anemia. After adjusting for age, stage, and optimal debulking status, the perichemotherapy hemoglobin level as a continuous variable was weakly associated with recurrence-free survival (adjusted hazard ratio [AHR], 0.98; P = 0.03), and as a categorical variable with both recurrence-free survival (AHR, 2.49; P = 0.003) and overall survival (AHR, 1.91; P = 0.02). The total number of transfusions was also weakly associated with poor recurrence-free survival (AHR, 1.06; P = 0.03). Conclusions: Our study is a retrospective analysis of the effects of anemia and transfusion on ovarian cancer. The rates of anemia in chemotherapy patients are higher than previously reported. Although maintaining average hemoglobin greater than 80 g/L during chemotherapy portends an improved overall survival, blood transfusion does not have any effect. The role of transfusion should therefore be limited to symptomatic patients while giving 1 unit at a time. Further prospective studies will be needed to confirm these results.